PERAN OTORITAS JASA KEUANGAN DALAM MENGAWASI RESIKO PEMBIAYAAN DALAM INVESTASI “BODONG” - Abd Kadir Arno; A Ziaul Assad (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2017)
This article gives an overview of the role of financial services authorities in monitoring the risk of financing from investment that occurs in the community, the data used in this article are primary data in the form of laws and books relating to financial services authorities and financial and material risks secondary in the form of other reference materials that support the writing of this article. This article uses in-depth analysis techniques, which are to thoroughly examine and analyze the context discussed in this article. The conclusion of this article is that in every investment activity carried out in the community, it will have potential risks in the future, especially when there is a fraudulent investment in the community, therefore to overcome the existence of financial services authorities have the following roles: how to disseminate and inform the public about the characteristics of fundraising and financing, through seminars, and the Group Focus Discussion by involving academics as presenters 2) Facilitating dispute resolution between parties to disputes related to financing carried out by communities in a fictitious investment 3) Making regulations (regulation) as a form of protection so that there are no fraudulent investment activities in the community and 4) Making Investment Alert Task Force (Satgas) in each province in the archipelago.